2020
DOI: 10.1017/s0954422420000268
|View full text |Cite
|
Sign up to set email alerts
|

The drivers, trends and dietary impacts of non-nutritive sweeteners in the food supply: a narrative review

Abstract: Poor diets, including excess added sugar consumption, contribute to the global burden of disease. Subsequently, many nutrition policies have been implemented to reduce added sugar intake and improve population health, including taxes, education, labelling and environmental interventions. A potential consequence of these policy actions is the substitution of added sugars with non-nutritive sweeteners (NNS) in a variety of foods and beverages. NNS are used to reduce the energy and sugar content of foods and beve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 314 publications
(504 reference statements)
1
37
0
Order By: Relevance
“…Comprising stakeholders from industry, government, and public health, the Partnership aims to encourage healthy eating and incentivize food manufacturers to make ‘positive changes’ [ 8 ]. Despite a broad suite of potential policy actions available to reduce added sugar consumption and improve diet quality, including taxation of SSB, education and food environment interventions [ 9 ], the Partnership has focused predominantly on policies that promote nutrient reformulation, including voluntary targets for packaged, processed foods the Health Star Rating (HSR) labelling system and controlling the portion size of certain products [ 10 ]. Reformulation can be either overt, in which nutrient-profile changes are advertised to the consumer, or covert, in which compositional changes are not promoted [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprising stakeholders from industry, government, and public health, the Partnership aims to encourage healthy eating and incentivize food manufacturers to make ‘positive changes’ [ 8 ]. Despite a broad suite of potential policy actions available to reduce added sugar consumption and improve diet quality, including taxation of SSB, education and food environment interventions [ 9 ], the Partnership has focused predominantly on policies that promote nutrient reformulation, including voluntary targets for packaged, processed foods the Health Star Rating (HSR) labelling system and controlling the portion size of certain products [ 10 ]. Reformulation can be either overt, in which nutrient-profile changes are advertised to the consumer, or covert, in which compositional changes are not promoted [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, observational studies have reported associations between NNS consumption and weight gain [ 28 , 29 , 30 , 31 ], changes to the gut microbiome [ 32 ] and type-two diabetes [ 33 , 34 ]. Relationships from observational studies are correlational and may be biased, as participants with existing morbidities may be more likely to consume NNS than those without [ 9 ]. Concerns have also been raised regarding the potential substitution effects of UPF containing NNS for nutritious whole foods, and the long-term impact this may have on dietary balance and population health [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Public health strategies to reduce sugar overconsumption include addressing factors that influence the purchasing of high sugar foods (restriction of marketing and price promotions); tax on high-sugar beverages; reformulation of the food supply (setting sugar benchmarks and monitoring sugar content and portion size reduction); consumer education campaigns to increase awareness and providing practical steps to reduce sugar intake [ 13 ]; and food labelling of added sugar content [ 14 , 15 ]. The food industry’s response to global sugar reduction recommendations has included a reduction in added sugar and the replacement of sugars with non-nutritive and low-calorie sweeteners.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, NNS add sweetness to foods with little or no energy, thereby reducing the sugar and energy content of products. Such foods may or may not be labelled as ‘diet’, ‘sugar-free’ or ‘low-joule/calorie’ and commonly contain one or more NNS in full or partial replacement of sugar [ 15 ]. A recent study of packaged food in Hong Kong noted that many foods containing NNS were not labelled ‘diet’ and therefore NNS may be consumed in larger amounts than previously thought [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation